Trump's Trade Policy, BREXIT, Corona Dynamics, EU Crisis and Declining Multilateralism - Paul J. J. Welfens (International Economics and Economic Policy, 2020)
Since 1991 there has been a reinforcement of the World Market Economy, not least since China and the, then new Russian Federation have joined the World Trade Organization and because of EU Eastern enlargement and ASEAN integration deepening, while the Transatlantic Trade and Investment Partnership (TTIP) and Trans-Pacific Partnership (TPP) negotiations seemed to indicate stronger regional integration dynamics. With the Trump Administration, the situation has changed dramatically as President Trump is supportive of neither multilateralism in general nor of the EU, which is weakened through BREXIT, in particular. Trump's focus on the US merchandise trade balance deficit is ill-placed and import tariffs imposed on China seem to be excessive as the optimum tariff rate is miscalculated on the basis of the traditional formula – while a new adequate formula would include the role of sectoral US outward FDI stocks. Asia, the EU and the US could define fighting the Corona World Recession as a global public good, but the United States is weakened in the corona pandemic crisis; the EU is facing serious problems in avoiding a Euro Crisis 2 problem and the exteuro750 billion EU loan package could undermine the Eurozone's stability while being inadequate to minimize the risk of a Euro Crisis 2. At the same time, the prospects for EU cooperation are declining due to political disappointment concerning the national corona pandemic policy in some member countries. An effective anti-corona pandemic policy would mean to organize a consistent EU-ASEAN cooperation or a G20 cooperation with a later extension to UN Organizations, including the IMF, the World Bank and the WHO. Post-corona, global governance could change strongly because of the long-term political scarring effects of the pandemic shock which could undermine EU and Western stability. Networked international leadership in support of multilateralism is an innovative – but difficult - option for EU-ASEAN-Mercosur.
Keywords: F13; F00; I10; E61; E62; 330; Trade policy; Brexit; Corona; EU; Multilateralism